Factors influencing millenials’ attitude towards cause-related marketing programmes and its impact on brand preference and brand loyalty - Piara Lal, Sandyah Rihan (2020)
The aim of this research is to identify factors that influence attitude of millennials towards Cause-Related Marketing (CRM) programmes and its impact on brand preferences and brand loyalty. The research investigates the antecedents of brand preference and brand loyalty with a mediating role of consumer attitude, simulating the Theory of Reasoned Action (TRA). Outcomes from the research depicted that individual value of consumers and their attitude towards CRM programmes has an influence on brand preferences and brand loyalty.